A machine‐learning algorithm to grade heart murmurs and stage preclinical myxomatous mitral valve disease in dogs - Andrew McDonald; Jose Novo Matos; Joel Silva; Catheryn Partington; Eve J. Y. Lo; Virginia Luis Fuentes; Lara Barron; Penny Watson; Anurag Agarwal (Journal of Veterinary Internal Medicine)
Abstract Background The presence and intensity of heart murmurs are sensitive indicators of several cardiac diseases in dogs, particularly myxomatous mitral valve disease (MMVD), but accurate interpretation requires substantial clinical expertise. Objectives Assess if a machine‐learning algorithm can be trained to accurately detect and grade heart murmurs in dogs and detect cardiac disease in electronic stethoscope recordings. Animals Dogs (n = 756) with and without cardiac disease attending referral centers in the United Kingdom. Methods All dogs received full physical and echocardiographic examinations by a cardiologist to grade any murmurs and identify cardiac disease. A recurrent neural network algorithm, originally trained for heart murmur detection in humans, was fine‐tuned on a subset of the dog data to predict the cardiologist's murmur grade from the audio recordings. Results The algorithm detected murmurs of any grade with a sensitivity of 87.9% (95% confidence interval [CI], 83.8%‐92.1%) and a specificity of 81.7% (95% CI, 72.8%‐89.0%). The predicted grade exactly matched the cardiologist's grade in 57.0% of recordings (95% CI, 52.8%‐61.0%). The algorithm's prediction of loud or thrilling murmurs effectively differentiated between stage B1 and B2 preclinical MMVD (area under the curve [AUC], 0.861; 95% CI, 0.791‐0.922), with a sensitivity of 81.4% (95% CI, 68.3%‐93.3%) and a specificity of 73.9% (95% CI, 61.5%‐84.9%). Conclusion and Clinical Importance A machine‐learning algorithm trained on humans can be successfully adapted to grade heart murmurs in dogs caused by common cardiac diseases, and assist in differentiating preclinical MMVD. The model is a promising tool to enable accurate, low‐cost screening in primary care.